Independence Referendum and Youth Party Membership in Scotland - Claire Breniaux (Revue LISA)
Party membership has declined since the end of the 20th century, going hand in hand with citizens’ increasing lack of interest in politics in Western democracies. Yet, in 2014 in Scotland, 84.6 per cent of voters voted in the Scottish independence referendum. As the turnout amongst young people was high and given that a lot of young Scots seemed to be mobilised by the referendum, this paper explores motivations to join political parties amongst young people in particular. It examines the reasons why young people join the Scottish National Party (SNP), the party whose membership surge was the most significant according to the study carried out by Mitchell, Bennie and Johns. Based on the theories of youth party membership as well as empirical research that was conducted from 2018 to 2020, this paper builds an SNP youth party membership model. It shows that independence is the most significant reason why young people become SNP members. Other variables play a role in their decision. Most of them are the main incentives and motivations usually identified by youth party membership scholars: individual, socio-economic resources, ideology, political socialisation, social motives like making friends, and career plans.